Prospective Study Of Power Generation From Natural Resources Using Hybrid System For Remote Area - Yaakub, Muhamad Faizal; Mohd Noh, Faridah Hanim; Mohd Zali, M. F.I.; Harun, Mohamad Haniff (Institute of Advanced Engineering and Science, 2020)
Living in the 21st century, electricity has become a need in every society level. However, numbers of the remote area, especially in third world countries still facing difficulty to reach a grid-connected electricity due to various reasons. As such, this paper presents a prospective study of generating an electrical energy that is converted by utilizing natural resources from the sky. It is realized by implementing a hybrid solar-rainwater harvesting system. Combination of 12Vdc 3Watt solar cells and 3.7 Vdc 129mW pico-hydro implemented in the work has given a great yield reaching average 921 milliwatts of energy produced by the natural resources.